The basso continuo : a survey of its origins in Italy and of its evolutionary diversification in Germany and France between 1650 and 1750 - Van Schoor, Richard John (College of Music, 2024)
I first became interested in the basso continua durir; ,; s ts to the Bartolomeo Cristofori Museum in Florence, where I hoped to trace :-,e development of the fortepiano and gain some insight into the circumstar:.es responsible for its appearance. Apart from an interest in the evolution of the pianc as an instrument, I was eager to examine the relationship between instrument and c-:,r:-,:J8ser with the demise of the basso continue: were compositions being inspired by S;Jecific instruments or were the instruments evolving in order to accommodate r!SV.' compositional styles and trends? Tracing the beginnings of the fortepiano necessitated a thorough look into the nature and function of the harpsichord, which was its immediate predecessor in terms of instrumental function. The following quote from the preface to Kuhnau's "Clavier Obung" (1692) suggests that in Gerr,any it had not been customary for the harpsichord to assume particular solo instrument status at the time: Warumb sollte man auff dem Claviere nicht eben, wie auff anderen lnstrumenten, dergleichen Sachen tractiren konnen? Da doch kein einziges Instrument dem Claviere die Praecedenz an Vollkommenheit jemals disputirlich gemacht hat. (Why shouldn't one be able to manage such things [as sonatas] on the Clavier just as on other instruments? As no single instrument has ever been able to challenge the Clavier's superiority in completeness.) Gerald Abraham, in an article on the harpsichord sonata also refers to this quote in terms of Kuhnau's role as a possible pioneer in the field and attributes the earliest harpsichord sonatas, roughly comparable to the Corellian sonata da chiesa, to him.1 Whether or not 2 Kuhnau was actually responsible for the first harpsichord sonatas, solo works for the instrument were at the time significantly increasing. This was also the case outside of Germany. The sonata in Bb (1692) and seven others from his "Frische Clavier FrOchte" (1696) thus seem to represent a bridge between the harpsichord's function as a basso continue instrument and the birth of its status as solo concert instrument